Accuracy Analysis of a Next-Generation Tissue Microarray on Various Soft Tissue Samples of Wistar Rats - Werry, Jan-Erik; Müller, Stefan; Wehrhan, Falk; Geppert, Carol-Immanuel; Frohwitter, Gesche; Kaemmerer, Peer W.; Möst, Tobias; Lutz, Rainer; Homm, Andi; Kesting, Marco Rainer; Weber, Manuel; Ries, Jutta (Applied Sciences, 2021)
This study aimed to investigate accuracy in different sectional planes of the TMA Grand Master (3DHISTECH) Workstation in various soft tissue samples collected from Wistar rats. A total of 108 animals were sacrificed and 963 tissue specimens collected from 12 soft-tissue types. A total of 3307 tissue cores were punched and transferred into 40 recipient TMA blocks. Digital image analysis was performed. Core loss showed a significant correlation with tissue type and was highest in skin tissue (p < 0.001), renal medulla and femoral artery, nerve, and vein bundle (p < 0.01). Overall, 231 of 3307 tissue cores (7.0%) were lost. Hit rate analysis was performed in 1852 punches. The target was hit completely, partially and missed totally by 89.4%, 7.2% and 2.2%. A total of 54.5% of punches had good accuracy with less than 200 mu m deviation from the centre of the targeted region and 92.6% less than 500 mu m. Accuracy decreases with greater sectional depth. In the deepest sectional plane of roughly 0.5 mm median depth, almost 90% of cores had a deviation below 500 mu m. Recommendations for automated TMA creation are given in this article. The ngTMA(R)-method has proven accurate and reliable in different soft tissues, even in deeper sectional layers.
CRIS-Team WoS Importer:2021-07-09

A new standardized critical size bone defect model in the pig forehead for comparative testing of bone regeneration materials - Möst, Tobias; Schlegel, Karl Andreas; Kesting, Marco Rainer; Fenner, Matthias; Lutz, Rainer; Beck, Daniele Machado; Nkenke, Emeka; von Wilmowsky, Cornelius (Clinical Oral Investigations, 2019)
Objectives: The preclinical study aimed to establish a standardized preclinical model to investigate osseous graft consolidation in defect configurations of limited regenerative capacity. Material and methods: Critical size defects (CSD) were prepared and titanium tubes inserted for defect separation from local bone in the forehead area of 18 pigs. Defects were filled with demineralized bovine bone mineral (DBBM) or served as empty controls and were covered with a resorbable collagen membrane (CM) or left untreated. Six randomly selected pigs were sacrificed after 4, 8 and 12 weeks. Specimens were histologically and histomorphometrically analysed focusing on newly formed bone (NFB), demineralized bovine bone mineral (DBBM) and soft tissue (ST) proportions. Results: Four weeks after defect preparation, no statistically significant difference concerning NFB quantity could be detected within the groups. Defects covered with the CM showed lower amounts of DBBM. After 6 and 12 weeks, defects augmented with DBBM in combination with a CM (8 weeks: 43.12 ± 4.31; 12 weeks: 43.05 ± 3.01) showed a statistically significant higher NFB rate compared to empty control defects covered with 8 weeks: 7.66 ± 0.59; 12 weeks or without a CM; 8 weeks: 8.62 ± 2.66; 12 weeks: 18.40 ± 2.40. CM application showed no significant impact on osseous defect regeneration or soft tissue formation. Superior NFB could be detected for basal aspect for several evaluation time points. Conclusions: The modification of CSD with titanium tubes represents a suitable model to imitate a one-wall defect regeneration situation. Clinical relevance: The established model represents a promising method to evaluate graft consolidation in one-wall defect configuration.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Animal model; Bone substitutes; Critical size defect; Demineralized bovine bone mineral

An ex vivo model for education and training of bilateral cleft lip surgery - Lutz, Rainer; Kesting, Marco Rainer; Weber, Manuel; Olmos, Manuel; Tasyürek, Deniz; Möst, Tobias; Bürstner, Jan; Schulz, Katja (BMC Medical Education, 2023)
Background: Bilateral cleft lip surgery is very challenging and requires a high level of skill, knowledge and experience. Existing high-fidelity simulation models that can be used by novice cleft surgeons to gain experience and expand their knowledge are rare and expensive. In this study, we developed a bilateral cleft lip model using porcine snout discs, which are available anywhere and inexpensive. Methods: Anatomic reference points of a patient with a bilateral cleft lip were superimposed with landmarks of the porcine snout disc on a foil template. The template was used to construct an ex vivo bilateral cleft lip model. Surgery was performed on the model according to Millard and the surgical steps were photodocumented analogous to two clinical cases of bilateral cleft lip surgery. The suitability of the model was further tested by twelve participants and evaluated using self-assessment questionnaires. Results: The bilateral cleft lip ex vivo model made of a porcine snout disc proved to be a suitable model with very low cost and ease of fabrication, as the template is reusable on any snout disc. The Millard procedure was successfully performed and the surgical steps of the lip plasty were simulated close to the clinical situation. Regarding the nasal reconstruction, the model lacks three-dimensionality. As a training model, it enhanced the participants comprehension of cleft surgery as well as their surgical skills. All participants rated the model as valuable for teaching and training. Conclusions: The porcine snout discs can be used as a useful ex vivo model for bilateral cleft lip surgery with limitations in the construction of the nose, which cannot be realistically performed with the model due to anatomical differences with humans. Benefits include a realistic tissue feel, the simulation of a multi-layered lip construction, a wide and rapid availability and low cost. This allows the model to be used by novice surgeons also in low-income countries. It is therefore useful as a training model for gaining experience, but also as a model for refining, testing and evaluating surgical techniques for bilateral lip plasty.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Bilateral cleft lip; Cadaver model; Cheiloplasty; Ex vivo model; Lip plasty; Porcine snout disc; Residency training; Skills lab; Surgical simulation; Teaching

An ex vivo model for education and training of unilateral cleft lip surgery. - Lutz, Rainer; Schulz, Katja; Weber, Manuel; Olmos, Manuel; Möst, Tobias; Bürstner, Jan; Kesting, Marco Rainer (BMC Medical Education, 2023)
BACKGROUND: Unilateral cleft lip surgery is a complex procedure, and the outcome depends highly on the surgeon's experience. Digital simulations and low-fidelity models seem inadequate for effective surgical education and training. There are only few realistic models for haptic simulation of cleft surgery, which are all based on synthetic materials that are costly and complex to produce. Hence, they are not fully available to train and educate surgical trainees. This study aims to develop an inexpensive, widely available, high-fidelity, ex vivo model of a unilateral cleft lip using a porcine snout disc. METHODS: A foil template was manufactured combining anatomical landmarks of the porcine snout disc and the anatomical situation of a child with a unilateral cleft. This template was used to create an ex vivo model of a unilateral cleft lip from the snout disc. Millard II technique was applied on the model to proof its suitability. The individual steps of the surgical cleft closure were photo-documented and three-dimensional scans of the model were analysed digitally. Sixteen surgical trainees were instructed to create a unilateral cleft model and perform a unilateral lip plasty. Their self-assessment was evaluated by means of a questionnaire. RESULTS: The porcine snout disc proved highly suitable to serve as a simulation model for unilateral cleft lip surgery. Millard II technique was successfully performed as we were able to perform all steps of unilateral cleft surgery, including muscle suturing. The developed foil-template is reusable on any porcine snout disc. The creation of the ex vivo model is simple and inexpensive. Self-assessment of the participants showed a strong increase in comprehension and an eagerness to use the model for surgical training. CONCLUSIONS: A porcine snout disc ex vivo model of unilateral cleft lips was developed successfully. It shows many advantages, including a haptic close to human tissue, multiple layers, low cost, and wide and rapid availability. It is therefore very suitable for teaching and training beginners in cleft surgery and subsequently improving surgical skills and knowledge. Further research is needed to finally assess the ex vivo model's value in different stages of the curriculum of surgical residency.
EVALuna2:567006

A Treatment Approach for Carotid Blowout Syndrome and Soft Tissue Reconstruction after Radiotherapy in Patients with Oral Cancer: A Report of 2 Cases - Möst, Tobias; Kesting, Marco Rainer; Rohde, Maximilian; Lang, Werner; Meyer, Alexander; Weber, Manuel; Lutz, Rainer (Journal of Clinical Medicine, 2023)
Background: This retrospective case series study aims to demonstrate a salvage technique for the treatment of carotid blow-out syndrome (CBS) in irradiated head and neck cancer patients with a vessel-depleted neck. Methods: Between October 2017 and October 2021, two patients (N = 2) with CBS were treated at our institution in a multidisciplinary approach together with the Department of Vascular Surgery. Patients were characterized based on diagnoses, treatment procedures, and the subsequent postoperative course. Results: Surgical emergency intervention was performed in both cases. The transition zone from the common carotid artery (CCA) to the internal carotid artery (ICA) was resected and reconstructed with a xenogic (case 1) or autogenic (case 2) interposition (end-to-end anastomosis). To allow reconstruction of the vascular defect, an additional autologous vein graft was anastomosed to the interposition graft in an end-to-side technique, allowing arterial anastomosis for a free microvascular flap without re-clamping of the ICA. Because of the intraoperative ICA reconstruction, none of the patients suffered a neurological deficit. Conclusions: The techniques presented in the form of two case reports allow for acute bleeding control, cerebral perfusion, and the creation of a vascular anastomosis option in the vessel-depleted neck.
CRIS-Team Scopus Importer:2023-05-26
Keywords: carotid blow out syndrome; irradiation; vessel graft; vessel-depleted neck

Beyond PD‐L1—Identification of Further Potential Therapeutic Targets in Oral Cancer - Weber, Manuel; Lutz, Rainer; Olmos, Manuel; Glajzer, Jacek; Baran, Christoph; Nobis, Christopher-Philipp; Möst, Tobias; Eckstein, Markus; Kesting, Marco Rainer; Ries, Jutta (Cancers, 2022)
Background: The involvement of immune cell infiltration and immune regulation in the progression of oral squamous cell carcinoma (OSCC) is shown. Anti‐PD‐1 therapy is approved for the treatment of advanced OSCC cases, but not all patients respond to immune checkpoint inhibi-tors. Hence, further targets for therapeutic approaches are needed. The number of identified cellular receptors with immune checkpoint function is constantly increasing. This study aimed to perform a comparative analysis of a large number of immune checkpoints in OSCC in order to identify possible targets for therapeutic application. Materials and Methods: A NanoString mRNA analysis was performed to assess the expression levels of 21 immune regulatory checkpoint molecules in OSCC tissue (n = 98) and healthy oral mucosa (NOM; n = 41). The expression rates were compared between the two groups, and their association with prognostic parameters was determined. Additionally, relevant correlations between the expression levels of different checkpoints were examined. Results: In OSCC tissue, significantly increased expression of CD115, CD163, CD68, CD86, CD96, GITRL, CD28 and PD‐L1 was detected. Additionally, a marginally significant increase in CD8 expression was observed. BTLA and PD‐1 levels were substantially increased, but the differential expression was not statistically significant. The expression of CD137L was significantly downregulated in OSCC compared to NOM. Correlations between immune checkpoint expression levels were demonstrated, and some occurred specifically in OSCC tissue. Conclusions: The upregulation of inhibitory receptors and ligands and the downregulation of activators could contribute to reduced effector T‐cell function and could induce local immunosuppression in OSCC. Increased expression of activating actors of the immune system could be explained by the increased infiltration of mye-loid cells and T‐cells in OSCC tissue. The analysis contributes to the understanding of immune es-cape in OSCC and reveals potential targets for oral cancer immunotherapy.
CRIS-Team Scopus Importer:2022-04-15
Keywords: head and neck cancer; HNSCC; immune checkpoints; immunotherapy; macro-phage; MDSC; OSCC; T‐cell

Case report: Patient specific combination of surgery and immunotherapy in advanced squamous cell carcinoma of the head and neck – a case series and review of literature - Olmos, Manuel; Lutz, Rainer; Büntemeyer, Tjark-Ole; Glajzer, Jacek; Nobis, Christopher-Philipp; Ries, Jutta; Möst, Tobias; Eckstein, Markus; Hecht, Markus; Gostian, Antoniu-Oreste; Erdmann, Michael; Foerster, Yannick; et al. (Frontiers in Immunology, 2022)
Background: Prognosis of patients with recurrent or metastatic head and neck cancer is generally poor. Adjuvant immunotherapy (IT) featuring immune checkpoint inhibition (ICI) is standard of care in advanced stage head and neck squamous cell carcinoma (HNSCC) and cutaneous squamous cell carcinoma (CSCC). ICI response rates in CSCC are described as higher than in HNSCC. IT is constantly shifting into earlier disease stages which confronts the surgeon with immunotherapeutically pre-treated patients. It is therefore becoming increasingly difficult to assess which patients with symptomatic tumor disease and a lack of curative surgical option might benefit from salvage surgery. Case presentations: The following 6 cases describe therapeutic decision-making regarding ICI and (salvage) surgery in patients with advanced stage HNSCC or CSCC. Cases A and B focus on neoadjuvant ICI followed by salvage surgery. In Cases C and D salvage surgery was performed after short-term stabilization with partial response to ICI. The last two cases (Cases E and F) address the surgical approach after failure of ICI. All cases are discussed in the context of the current study landscape and with focus on individual decision-making. For better understanding, a timetable of the clinical course is given for each case. Conclusions: ICI is rapidly expanding its frontiers into the neoadjuvant setting, frequently confronting the surgeon with heavily pretreated patients. Salvage surgery is a viable therapeutic concept despite the rise of systemic treatment options. Decision-making on surgical intervention in case of a salvage surgery remains an individual choice. For neoadjuvant ICI monitoring regarding pathological tumor response or tumor necrosis rate, we suggest correlation between the initial biopsy and the definite tumor resectate in order to increase its significance as a surrogate marker. Scheduling of neoadjuvant ICI should be further investigated, as recent studies indicate better outcomes with shorter time frames.
CRIS-Team Scopus Importer:2022-11-25
Keywords: anti-PD 1; checkpoint inhibition; CSCC; HNSCC; immunotherapy; neoadjuvant; OSCC; salvage surgery

Comparison of the 7th and revised 8th UICC editions (2020) for oral squamous cell carcinoma: How does the reclassification impact staging and survival? - Struckmeier, Ann-Kristin; Eichhorn, Philip; Agaimy, Abbas; Buchbender, Mayte; Möst, Tobias; Lutz, Rainer; Kesting, Marco Rainer (Virchows Archiv, 2024)
Since its introduction in 1968, the TNM (tumor, node, metastasis) classification established by the International Union Against Cancer has provided a consistent framework for staging of oral squamous cell carcinoma (OSCC). The introduction of the 8th edition in 2017 brought about significant modifications, encompassing the integration of depth of invasion (DOI) and extranodal extension (ENE) into the T and N classifications. Further, the UICC the criteria for the T3 and T4a categories were amended in 2020. This study aimed to evaluate the impact of reclassification on staging and, subsequently, the survival of patients with OSCC. Primary OSCCs from 391 patients were classified according to the 7th and revised 8th UICC editions (2020). Stage migration was assessed, and stage-specific progression-free survival (PFS) and overall survival (OS) were evaluated using the Kaplan–Meier method. The log-rank test was used to compare the different stages. Cox-proportional hazard modeling was used to compare the two editions. Incorporating the DOI into the T classification resulted in an upstaging of 77 patients, constituting 19.69% of the cohort. In addition, 49 (12.53%) patients experienced an upstaging when considering ENE in the N classification. Consequently, 103 patients underwent upstaging in UICC staging, accounting for 21.74% of cases. Upstaging mainly occurred from stage III to IVA (26.92%) and from stage IVA to IVB (31.78%). Upon comparing the categories in survival analysis, significant differences in OS and PFS were especially observed between stage IVB and lower stages. When examining the hazard ratios, it became evident that UICC 8 stage IVB is burdened by a 5.59-fold greater risk of disease progression than stage I. Furthermore, UICC 8 stage IVB exhibits a 3.83 times higher likelihood of death than stage I disease. We demonstrated significant stage migration from the 7th to the revised 8th UICC edition. Overall, incorporating DOI and ENE into the T and N classifications represents a substantial clinical advancement, leading to a more accurate staging of OSCC patients. Both staging systems exhibited statistically significant discrimination between stages; however, the 8th UICC edition allowed for a more precise categorization of patients based on their prognosis and led to enhanced hazard discrimination, particularly within higher stages.
CRIS-Team Scopus Importer:2024-02-02
Keywords: Oral squamous cell carcinoma; Staging; TNM classification; UICC

Correction to: Anatomical locations in the oral cavity where surgical resections of oral squamous cell carcinomas are associated with a close or positive margin—a retrospective study (Clinical Oral Investigations, (2018), 22, 4, (1625-1630), 10.1007/s00784-018-2424-z) - Kerker, Florian; Adler, Werner; Brunner, Kathrin; Möst, Tobias; Wurm, Matthias; Nkenke, Emeka; Neukam, Friedrich Wilhelm; von Wilmowsky, Cornelius (Clinical Oral Investigations, 2019)
The following note was inadvertently omitted from the published paper: This work was performed in (partial) fulfillment of the requirements for the first author’s obtaining the degree Dr. med. dent.
CRIS-Team Scopus Importer:2019-05-02

Corrigendum to “Establishment of a new pull-out strength testing method to quantify early osseointegration - An experimental pilot study” [J Cranio-Maxillofacial Surg 43 (10) (December 2015) 1966–1973](S1010518215003364)(10.1016/j.jcms.2015.10.005) - Nonhoff, J.; Möst, Tobias; Schmitt, Christopher; Weisel, T.; Bauer, S.; Schlegel, K. A. (Journal of Cranio-Maxillofacial Surgery, 2019)
The authors regret an incorrect information in the “Material and Methods” section concerning the mentioned German breeding company (‘Breeding Company Renner, Franconia’). The correct breeding company is the ‘National Centre for Agricultural Research and Innovation’ (Nemzeti Agrárkutatási és Innovácios Központ Állattenyésztési, Takarmányozási és Húsipari Kutatóintézet, 2053 Herceghalom Gesztenyés u. 1., Hungary). The study has been performed in Hungary and the mentioned number belongs to the ‘Pest country government department for food safety and animal health, Hungary’. The authors would like to apologise for any inconvenience caused.
EVALuna2:203644

COVID-19 pandemic and its impact on dental education: digitalization - progress or regress? Example of an online hands-on course - Oetter, Nicolai; Möst, Tobias; Weber, Manuel; Buchbender, Mayte; Rohde, Maximilian; Foerster, Yannick; Bauerschmitz, Charlotte; Röschmann, Nico; Adler, Werner; Rau, Andrea; Meyerolbersleben, Marion; Kesting, Marco Rainer; et al. (BMC Medical Education, 2022)
BACKGROUND: Due to the SARS-CoV-2 pandemic and the accompanying contact restrictions, a new challenge arose for dental education. Despite the limited overall situation, it must be ensured that, in addition to theoretical content, practical skills in particular continue to be taught. Therefore, the aim of this study was to develop and implement an online hands-on course for dental students that ensures practical training, even during the pandemic. METHODS: The newly developed course was held from April 2020 to March 2021. A total of six groups (each consisting of approximately 40-50 students) took part in the course. The participating students were in their 3rd, 4th or 5th year of study. The course taught theoretical basics (via an online platform) and promoted the learning of practical/surgical techniques on models such as bananas, pork bellies, or chicken thighs with live demonstrations (via ZOOM) and interactive post-preparation by students at home (and in a rotating small group of 3-7 students on site). Student self-evaluation (at the beginning and end of the course) and course evaluation were performed using questionnaires. The learning success was analyzed (through self-evaluations) using Wilcoxon signed-rank tests (significance level alpha = 0.05). RESULTS: Concerning students´ self-evaluations, the theoretical knowledge, general surgical skills (such as surgical instrument handling), and specific surgical skills (such as performing a kite flap) improved during the course, with significant results (p < 0.001 for each). About 60% of the students rated the course overall as excellent (grades 9 or 10 on a Likert scale of 1 to 10). The technical implementation of the course was rated with a median of 9 (= very good, on a Likert scale of 1 to 10). 38.5% described the applicability of the skills learned for their later professional life as extremely good. CONCLUSIONS: The results of this work suggest that, within the limitations of this study, the introduced concept of an online hands-on course could be an appropriate form of teaching practical dental skills, even during a pandemic. Further research is needed in the field of digital education for dental students.
Created from Fastlane, Scopus look-up
Keywords: Asynchronous; Coronavirus; Dentistry; Digital; Education; Pandemic; Synchronous

Development of a porcine training model for microvascular fasciocutaneous free flap reconstruction - Nobis, Christopher-Philipp; Grottschreiber, Katharina; Olmos, Manuel; Möst, Tobias; Weber, Manuel; Kesting, Marco Rainer; Lutz, Rainer (Head & Face Medicine, 2024)
Background: In reconstructive surgery, improvements are needed in the effective teaching of free flap surgery. There is a need for easily accessible and widely available training without high financial costs or ethical concerns while still providing a realistic experience. Our aim was to develop an appropriate training model for microvascular flaps. Methods: We identified pig head halves as most appropriate regarding availability, cost, and realism. These accrue largely by the food industry, so no animals need to be sacrificed, making it more ethical from an animal welfare perspective. We evaluated the suitability as flap donor site and analyzed the vascular anatomy of 51 specimens. Results: Anatomical evaluation revealed a reliable and constant vascular anatomy, allowing the design of a flap model that can effectively illustrate the entire process of microvascular flap surgery. The process was divided into 6 key steps. The flap can be harvested after marking the vascular pedicle 5.3 cm from the lateral corner of the mouth. Skin island design and subsequent tissue dissection follow until a fasciocutaneous flap is raised, similar to a radial flap. Upon completion of flap harvesting, it can be freely transferred for defect reconstruction. Microvascular anastomosis can be performed on recipient vessels in the cervical region, and the difficulty can be individually adjusted. Conclusions: The developed training model is a reasonable compromise in terms of surgical realism, availability, didactic value, and cost/time effectiveness. We believe it is a powerful and effective tool with high potential for improving surgical education and training.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Free flap surgery; Microvascular flap; Oral and maxillofacial surgery; Plastic and reconstructive surgery; Porcine animal model; Surgical training model

Diabetes mellitus negatively affects peri-implant bone formation in the diabetic domestic pig - von Wilmowsky, Cornelius; Stockmann, Philipp; Harsch, Igor; Amann, Kerstin Ute; Metzler, Philipp; Lutz, Rainer; Möst, Tobias; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Journal of Clinical Periodontology, 2011)
Aim: Diabetes mellitus is classified as a relative contraindication for implant treatment, and higher failure rates have been seen in diabetic patients. The aim of the present study was to investigate the effect of diabetes on peri-implant bone formation in an animal model of human bone repair. Materials and Methods: Diabetes was induced by an intra-venous application of streptozotocin (90 mg/kg) in 15 domestic pigs. Implants were placed after significant histopathological changes in the hard and soft tissues were verified. The bone-implant contact (BIC), peri-implant bone mineral density (BMD), and expression of collagen type-I and osteocalcin proteins were qualitatively evaluated 4 and 12 weeks after implantation. Fifteen animals served as healthy controls. Results: Diabetes caused pathological changes in the soft and hard tissues. The BIC and BMD were significantly reduced in the diabetic group after 4 and 12 weeks. Collagen type-I was increased in the diabetic group at both time points, whereas osteocalcin was reduced in the diabetic group. Conclusions: Poorly controlled diabetes negatively affects peri-implant bone formation and bone mineralization. These findings have to be taken into consideration for diabetic patients with an indication for implant therapy. © 2011 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2024-05-13
Keywords: bone; diabetes; implants; osseointegration; pig

Diagnostic accuracy of contrast-enhanced computed tomography in assessing cervical lymph node status in patients with oral squamous cell carcinoma - Struckmeier, Ann-Kristin; Yekta, Ebrahim; Agaimy, Abbas; Kopp, Markus; Buchbender, Mayte; Möst, Tobias; Lutz, Rainer; Kesting, Marco Rainer (Journal of Cancer Research and Clinical Oncology, 2023)
Objective: Accurate preoperative prediction of lymph node (LN) status plays a pivotal role in determining the extension of neck dissection (ND) required for patients with oral squamous cell carcinoma (OSCC). This study aims to evaluate the diagnostic accuracy of contrast-enhanced computed tomography (CT) in detecting LN metastases (LNMs) and to explore clinicopathological factors associated with its reliability. Methods: Data from 239 patients with primary OSCC who underwent preoperative CT and subsequent radical surgery involving ND were retrospectively reviewed. Suspicious LNs were categorized into three groups: accentuated (< 10 mm), enlarged (≥ 10 mm), and melted. Statistical analysis encompassing correlation and comparative analysis, and determination of sensitivity, specificity, PPV, and NPV were performed. Results: Overall, sensitivity was significantly higher in the accentuated LNs group (83.54%) compared to the melted LNs group (39.24%, p < 0.05, t test). Conversely, specificity was significantly higher in the melted LNs group (98.19%) compared to the accentuated LNs group (55.15%, p < 0.05, t test). Accentuated LNs exhibited a false negative rate of 13.00%. False positive rates were 51.80%, 30.26% and 8.82%, respectively. Diagnostic accuracy for detecting LNMs in level IIa and IIb exceeded that of level III. Patients with solely accentuated LNs were more likely to have a small, well-differentiated tumor. However, no distinctions emerged in terms of the occurrence of T4 tumors among the three groups. Conclusion: CT proves sufficient to predict LNMs in patients with OSCC. Looking ahead, the potential integration of artificial intelligence and deep learning holds promise to further enhance the reliability of CT in LNMs detection. However, this prospect necessitates further investigation.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Computed tomography; Diagnostic accuracy; Lymph node metastasis; Oral squamous cell carcinoma

Early MDO with a Virtually Planned Distractor in a Neonate with Pierre Robin Sequence - Lutz, Rainer; Olmos, Manuel; Schmidt, Joachim; Morhart, Patrick; Nobis, Christopher-Philipp; Möst, Tobias; Kesting, Marco Rainer; Weber, Manuel (Plastic and Reconstructive Surgery Global Open, 2022)
Pierre Robin sequence (PRS) is characterized by mandibular micrognathia, glossoptosis, and airway obstruction. We report a case of a female infant with PRS in combination with deletion of chromosome 4q and cardiac insufficiency due to an atrioventricular septum defect. The child was transferred to our center from a peripheral hospital with respiratory insufficiency. Initially, respiration was ensured using a continuous positive airway pressure (CPAP) device because a Tuebingen plate was not tolerated. After a pediatric cardiac surgery intervention, CPAP ventilation proved to be insufficient, and the young patient had to be resuscitated and endotracheal intubation was required for recurrent severe respiratory failure. To avoid tracheostomy, an interdisciplinary decision was made to perform an early mandibular distraction. In the fifth week of life, two patient-specific internal distractors were implanted after prior virtual surgery planning. This approach allows for shorter surgical time through preoperative vector planning and fabrication of a patient-specific distractor, in combination with reduced morbidity through maximum protection of adjacent structures such as the tooth follicles and inferior alveolar nerves. An advancement of the mandible by 15mm could be achieved within 2 weeks. Thereafter, the small patient could be extubated successfully, and there was no further episode of major respiratory insufficiency. We demonstrate that mandibular early distraction with a patient-specific distractor is a successful method to treat severe respiratory insufficiency in PRS, and it can prevent the necessity for tracheostomy with the resulting disadvantages. We provide details concerning our therapeutic algorithm, metric analyses, and a discussion of relevant literature.
CRIS-Team WoS Importer:2022-06-17

Expression of inflammatory mediators in biofilm samples and clinical association in inflammatory bowel disease patients—a preliminary study - Buchbender, Mayte; Fehlhofer, Jakob Paul; Proff, Peter; Möst, Tobias; Ries, Jutta; Hannig, Matthias; Neurath, Markus; Gund, Madline; Atreya, Raja; Kesting, Marco Rainer (Clinical Oral Investigations, 2021)
Objectives: Inflammatory bowel disease (IBD) has multiple impacts on soft and hard tissues in the oral cavity. The aim of this study was to analyze the expression of cytokines in biofilm samples from patients suffering from IBD and compare them to healthy patients. It was hypothesized that different cytokine expression levels and clinical associations might be drawn. Material and methods: A total of 56 biofilm samples from three different patient cohorts (group 0 = healthy, HC n = 30; group 1 = Crohn’s disease, CD, n = 19; group 2 = ulcerative colitis, UC, n = 7) were examined for the expression levels of the cytokine interleukins IL-2, -6, and -10; matrix metalloproteinases 7 and 9; and surface antigens CD90/CD11a by quantitative real-time PCR and according to clinical parameters (plaque index, BOP, PD, DMFT, CAL). Relative gene expression was determined using the ∆∆CT method. Results: The mean BOP values (p = 0.001) and PD (p = 0.000) were significantly higher in the CD group compared to controls. Expression of IL-10 was significantly higher in the CD (p = 0.004) and UC groups (p = 0.022). Expression of MMP-7 was significantly higher in the CD group (p = 0.032). IBD patients treated with TNF inhibitors (p = 0.007) or other immunosuppressants (p = 0.014) showed significant overexpression of IL-10 compared to controls. Conclusion: Different expression levels of IL-10 and MMP-7 were detected in plaque samples from IBD patients. As only BOP was significantly increased, we conclude that no clinical impairment of periodontal tissue occurred in IBD patients. Clinical relevance: With the worldwide increasing incidence of IBD, it is important to obtain insights into the effects of the disease on the oral cavity. The study was registered (01.09.2020) at the German clinical trial registry (DRKS00022956). Clinical trial registration: The study is registered at the German clinical trial registry (DRKS00022956).
CRIS-Team Scopus Importer:2021-08-20
Keywords: Crohn’s disease; Cytokine expression; Oral biofilm; Periodontitis; Ulcerative colitis

Frequency of the necessity of dentoalveolar surgery or conservative treatment in patients before kidney transplantation depending on the duration of dialysis and causative nephrological disease - Möst, Tobias; Lutz, Rainer; Jahn, Arne Eric; Heller, Katharina M.; Schiffer, Mario; Adler, Werner; Deschner, James; Weber, Manuel; Kesting, Marco Rainer (Clinical Oral Investigations, 2021)
Objectives: This retrospective study evaluates intraoral surgical and conservative treatment need in patients with a chronic kidney end-stage disease, depending on the duration of dialysis treatment and the causative nephrological disease. Material and methods: This study is based on data of patients referred to the Department of Oral and Maxillofacial Surgery of the University Hospital Erlangen, Germany, prior to kidney transplantation between January 2015 and March 2020. The necessity for oral surgical or dental therapy was determined by clinical and radiological examinations. Data on renal replacement therapy, cause of underlying renal disease, lifestyle, and general health were collected. Results: Data of N = 89 patients demonstrated that surgical treatment need depends on dialysis duration (p = 0.042). Patients, who had been dialyzing for 2 to 3 years showed the highest need for surgical intervention (80.0%; p = 0.024), followed by dialysis patients with a dialysis time of more than 3 years (48.1%). Similarly, dialysis patients in the second or third year of dialysis had the highest need for conservative treatment (73.3%; p > 0.05), followed by 55.6% of dialysis patients in the third year of dialysis. Conclusions: Operative and conservative treatment is essential to optimize subsequent kidney transplantation. The greatest necessity could be detected for patients in the second and third years of dialysis. Clinical relevance: Oral health addressing surgical and conservative treatment need depends on the duration of dialysis in patients with a chronic kidney end-stage disease.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Immunosuppression; Kidney; Oral health; Organ transplantation

Gingiva thickening with a porcine collagen matrix in a preclinical dog model: Histological outcomes - Schmitt, Christian M.; Schlegel, Karl Andreas; Gammel, Lisa; Möst, Tobias (Journal of Clinical Periodontology, 2019)
Aim To compare 10-month histological and immunohistological outcomes after soft tissue thickening around teeth with a porcine collagen matrix (CM) versus a subepithelial connective tissue graft (SCTG). Material and Methods In eight beagle dogs, soft tissue thickening of the buccal gingiva of upper canines was performed with the SCTG or the CM. Connective tissue thickness (CTT) was histomorphometrically measured in the augmented regions. The augmented connective tissues were also histologically characterized and the collagen I and vascular endothelial growth factor (VEGF) expressions immunohistologically quantified. Results CTT significantly differed between groups (SCTG: 1.32 mm +/- 0.44 mm; CM: 1.06 mm +/- 0.27 mm; p = .008). Descriptive histological analyses revealed mature connective tissue that did not differ between groups. Immunohistological quantification of collagen I and VEGF expressions in the connective tissue also revealed no significant inter-group differences (collagen I: SCTG, 32.64% +/- 7.09% vs. CM, 30.57% +/- 7.83%; VEGF: SCTG, 39.06% +/- 7.27% vs. CM, 37.15% +/- 9.80%). Conclusion SCTG is superior to CM with regard to CTT in this experimental model. The CM and the SCTG lead to comparable connective tissue quality ten months after connective tissue thickening.
CRIS-Team WoS Importer:2019-10-25

Hartgewebeaugmentationen: Materialwahl - Schlegel, Karl Andreas; Wiltfang, Jörg; Lutz, Rainer; Schmitt, Christian; Möst, Tobias (Implantologie, 2016)
Long-term dental implant success depends on bone quality and quantity. Insufficient bone quantity makes pre- or intraoperative augmentative procedures necessary. For this purpose, autologous, allogeneic, xenogeneic, and alloplastic bone substitute materials (BSMs) are available, which differ in their capacity for osteogenesis, osteoconduction, and osteoinduction. Due to superior regenerative potential, autologous bone grafts represent the gold-standard. However, since autologous bone grafting is associated with increased patient morbidity, non-autologous BSMs are increasingly applied in implantology. Appropriate material selection, treatment planning, and application of patient considerations requires knowledge of the characteristics of the selected BSMs.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Allograft; Autograft; Bone substitute material (BSM); Grafting- procedures; Xenograft

Implants in the elderly patient - Schlegel, Karl Andreas; Schmitt, Christian; Möst, Tobias (Implantologie, 2020)
In our daily practice more and more patients show up who have received dental implants thirty or fourty years ahead. These patients are today related as "golden agers". At the same time in our days we can see that age related contraindications for implants are very liberal and no definite age limitation is valide any more. With some cases treated in the own office the reliability and problems of such aged patients should be highlighted. Also the question "quality of life" versus potential risks of these therapy options should be counterbalanced and at least when planning new implant borne rehablitations should be brought into consideration.
CRIS-Team WoS Importer:2021-02-05

Implants in the elderly patient Implantate beim hochbetagten patienten-Fluch oder segen?! fallserie hochbetagter patienten - Schlegel, Karl Andreas; Schmitt, Christian; Möst, Tobias (Implantologie, 2020)
In our daily practice more and more patients show up who have received dental implants thirty or fourty years ahead. These patients are today related as "golden agers". At the same time in our days we can see that age related contraindications for implants are very liberal and no definite age limitation is valide any more. With some cases treated in the own office the reliability and problems of such aged patients should be highlighted. Also the question "quality of life" versus potential risks of these therapy options should be counterbalanced and at least when planning new implant borne rehablitations should be brought into consideration.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Age; Complications; Implants; Peri-implant mucositis; Peri-implantitis; Risk analysis

Importance of the PD-1/PD-L1 Axis for Malignant Transformation and Risk Assessment of Oral Leukoplakia - Ries, Jutta; Agaimy, Abbas; Wehrhan, Falk; Baran, Christoph; Bolze, Stella; Danzer, Eva; Frey, Silke; Jantsch, Jonathan; Möst, Tobias; Büttner-Herold, Maike; Wickenhauser, Claudia; Kesting, Marco Rainer; et al. (Biomedicines, 2021)
Background: The programmed cell death ligand 1/programmed cell death receptor 1 (PD-L1/PD-1) Immune Checkpoint is an important modulator of the immune response. Overexpression of the receptor and its ligands is involved in immunosuppression and the failure of an immune response against tumor cells. PD-1/PD-L1 overexpression in oral squamous cell carcinoma (OSCC) compared to healthy oral mucosa (NOM) has already been demonstrated. However, little is known about its expression in oral precancerous lesions like oral leukoplakia (OLP). The aim of the study was to investigate whether an increased expression of PD-1/PD-L1 already exists in OLP and whether it is associated with malignant transformation. Material and Methods: PD-1 and PD-L1 expression was immunohistologically analyzed separately in the epithelium (E) and the subepithelium (S) of OLP that had undergone malignant transformation within 5 years (T-OLP), in OLP without malignant transformation (N-OLP), in corresponding OSCC and in NOM. Additionally, RT-qPCR analysis for PD-L1 expression was done in the entire tissues. Additionally, the association between overexpression and malignant transformation, dysplasia and inflammation were examined. Results: Compared to N-OLP, there were increased levels of PD-1 protein in the epithelial and subepithelial layers of T-OLP (PE = 0.001; PS = 0.005). There was no significant difference in PD-L1 mRNA expression between T-OLP and N-OLP (p = 0.128), but the fold-change increase between these groups was significant (Relative Quantification (RQ) = 3.1). In contrast to N-OLP, the PD-L1 protein levels were significantly increased in the epithelial layers of T-OLP (p = 0.007), but not in its subepithelial layers (p = 0.25). Importantly, increased PD-L1 levels were significantly associated to malignant transformation within 5 years. Conclusion: Increased levels of PD-1 and PD-L1 are related to malignant transformation in OLP and may represent a promising prognostic indicator to determine the risk of malignant progression of OLP. Increased PD-L1 levels might establish an immunosuppressive microenvironment, which could favor immune escape and thereby contribute to malignant transformation. Hence, checkpoint inhibitors could counteract tumor development in OLP and may serve as efficient therapeutic strategy in patients with high-risk precancerous lesions.
CRIS-Team WoS Importer:2021-03-19

In-vitro evaluation of Polylactic acid (PLA) manufactured by fused deposition modeling - Wurm, Matthias; Möst, Tobias; Bergauer, Bastian; Rietzel, Dominik; Neukam, Friedrich Wilhelm; Cifuentes, Sandra C.; von Wilmowsky, Cornelius (Journal of Biological Engineering, 2017)
With additive manufacturing (AM) individual and biocompatible implants can be generated by using suitable materials. The aim of this study was to investigate the biological effects of polylactic acid (PLA) manufactured by Fused Deposition Modeling (FDM) on osteoblasts in vitro according to European Norm / International Organization for Standardization 10,993-5.Human osteoblasts (hFOB 1.19) were seeded onto PLA samples produced by FDM and investigated for cell viability by fluorescence staining after 24 h. Cell proliferation was measured after 1, 3, 7 and 10 days by cell-counting and cell morphology was evaluated by scanning electron microscopy. For control, we used titanium samples and polystyrene (PS).Cell viability showed higher viability on PLA (95,3% ± 2.1%) than in control (91,7% ±2,7%). Cell proliferation was highest in the control group (polystyrene) and higher on PLA samples compared to the titanium samples. Scanning electron microscopy revealed homogenous covering of sample surface with regularly spread cells on PLA as well as on titanium.The manufacturing of PLA discs from polylactic acid using FDM was successful. The in vitro investigation with human fetal osteoblasts showed no cytotoxic effects. Furthermore, FDM does not seem to alter biocompatibility of PLA. Nonetheless osteoblasts showed reduced growth on PLA compared to the polystyrene control within the cell experiments. This could be attributed to surface roughness and possible release of residual monomers. Those influences could be investigated in further studies and thus lead to improvement in the additive manufacturing process. In addition, further research focused on the effect of PLA on bone growth should follow. In summary, PLA processed in Fused Deposition Modelling seems to be an attractive material and method for reconstructive surgery because of their biocompatibility and the possibility to produce individually shaped scaffolds.
EVALuna2:24438

Occult metastasis is no burden factor in oral squamous cell carcinoma patients when adhering to a standardized approach in neck dissection - Struckmeier, Ann-Kristin; Buchbender, Mayte; Möst, Tobias; Lutz, Rainer; Agaimy, Abbas; Kesting, Marco Rainer (Clinical Oral Investigations, 2024)
Objectives: Management of the neck in patients with oral squamous cell carcinoma (OSCC) is pivotal to oncologic control and survival. However, there is controversy regarding necessity of neck dissection (ND) in patients with clinically node-negative neck. We aimed to assess risk factors for occult metastasis and to explore whether the presence of occult lymph node metastases (LNMs) has an impact on recurrence and survival. Material and methods: A retrospective cohort study was performed including patients with primary OSCC who underwent radical tumor resection and ND in a high-volume center adhering to the prevailing German guideline. The ND was performed according to a standardized approach. Results: Four hundred twenty-one patients with primary surgically treated OSCC were included. The incidence of occult metastasis was 14.49%. A pathological T stage > 1 (multivariate analysis, odds ratio (OR) 3.958, p = 0.042) and the presence of extranodal extension in LNMs (multivariate analysis, OR 0.287, p = 0.020) were identified as independent risk factors for occult metastasis. When comparing patients with and without occult metastasis, there were no significant differences in terms of progression-free survival (log-rank, p = 0.297) and overall survival (log-rank, p = 0.320). There were no cases of ipsilateral neck recurrence. One patient developed contralateral neck metastasis; however, he initially presented with a unilateral pT1 pN0 tumor. Conclusions: Overall, our findings suggest that conducting a standardized approach in ND should be applied in terms of management of the neck in order to maintain survival rates and to prevent neck recurrence in OSCC patients. Clinical relevance. None of the risk factors for occult metastasis can be reliably assessed preoperatively. Although elective ND does not guarantee the complete prevention of neck recurrence, it increases the likelihood of either timely removal of micrometastases or strengthens the justification for adjuvant therapy. Consequently, this approach leads to improvements in clinical outcomes.
CRIS-Team Scopus Importer:2024-02-02
Keywords: Lymph node metastasis; Neck dissection; Occult metastasis; Oral squamous cell carcinoma

Oral health of patients suffering from end-stage solid organ insufficiency prior to solid organ re-transplantation: a retrospective case series study - Möst, Tobias; Lutz, Rainer; Jahn, Arne Eric; Heller, Katharina M.; Schiffer, Mario; Adler, Werner; Deschner, James; Weber, Manuel; Kesting, Marco Rainer (BMC Oral Health, 2021)
Background: The oral health of organ transplanted patients before organ re-transplantation is largely unknown. This retrospective clinical study evaluates the necessity for intraoral surgical intervention and/or conservative treatment in candidates awaiting organ re-transplantation, both for graft failure and for reasons of another upcoming solid organ transplantation (renal or non-renal). Methods: From January 2015 to March 2020 n = 19 transplant recipients in evaluation on the waiting list for solid organ re-transplantation could be included in the retrospective case series study. Using clinical and radiological examinations, necessity for oral surgical or conservative dental treatment was evaluated. On the basis of anamnesis data, current kidney function, renal replacement treatment (RRT), and medication, a risk profile for several patient subgroups was created. Results: The clinical and radiological examinations showed a conservative and/or surgical treatment need in n = 13 cases (68.42%). In n = 7 cases (36.84%) surgical intervention was recommended due to residual root remnants (n = 5), unclear mucosal changes (n = 1), and periimplantitis (n = 1). In n = 16 recipients (84.2%) RRT (n = 15 hemodialysis; n = 1 peritoneal dialysis) had been performed. N = 14 recipients (73.68%) received immunosuppressants. In n = 1 patient (5.3%) displayed intraoral and n = 4 patients (21.1%) extraoral neoplasms due to drug-induced immunosuppression. Conclusions: Solid organ transplant recipients with renal failure present a complex treatment profile due to a double burden of uremia plus immunosuppressants. In cases of surgical treatment need a hospitalized setting is recommended, where potentially necessary follow-up care and close cooperation with disciplines of internal medicine is possible in order to avoid surgical and/or internal complications.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Immunosuppression; Oral health; Organ transplantation

Osseointegration of SLActive implants in diabetic pigs - Schlegel, Karl Andreas; Prechtl, Christopher; Möst, Tobias; Seidl, C.; Lutz, Rainer; von Wilmowsky, Cornelius (Clinical Oral Implants Research, 2013)
Objectives: Diabetes mellitus is currently classified as a relative contraindication for implant treatment because of microangiopathies with the consequence of impaired bone regeneration and higher rates of implant failure. The study aim was to investigate peri-implant bone formation in a diabetic animal model in comparison to healthy animals and to evaluate the differences between conventional (SLA®) and modified (SLActive®) titanium implant surfaces on osseointegration. Material and methods: Each six implants were placed in the calvaria of 11 diabetic and 4 healthy domestic pigs. At 30 and 90 days after implant placement, the bone-to-implant contact (BIC) and bone density (BD) were appraised. Additionally, the expression of the bone-matrix proteins collagen type I and osteocalcin was evaluated at both points in time by using immunohistochemical staining methods. Results: Overall, BIC was reduced in the diabetic group at 30 and 90 days. After 90 days, the SLActive® implants showed significantly higher BICs compared with the SLA® implants in diabetic animals. Peri-implant BD was higher in the SLActive® group at 30 and 90 days in healthy and diabetic animals. Collagen type I protein expression was higher using SLA® implants in diabetic pigs at 30 days. Values for osteocalcin expression were not consistent. Conclusions: The results indicate the negative effect of untreated diabetes mellitus on early osseointegration of dental implants. The modified SLA® surface (SLActive®) elicited an accelerated osseointegration of dental implants, suggesting that a better prognosis for implant treatment of diabetic patients is possible. © 2011 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Bone-to-implant contact; Collagen; Diabetes mellitus; Implant; Osteocalcin; SLA; SLActive

Osseous ingrowth in allogeneic bone blocks applied for vertical bone augmentation: a preclinical randomised controlled study - Möst, Tobias; Frabschka, Johanna; Kesting, Marco Rainer; Schmitt, Christian; Frohwitter, Gesche; Lutz, Rainer; Schlegel, Karl Andreas (Clinical Oral Investigations, 2019)
Objectives: The aim of the present study was the qualitative and quantitative evaluation of osseous graft consolidation using allogeneic bone blocks for vertical bone augmentation in an animal model. Material and methods: Standardised allogeneic and autologous bone blocks were fixed on the frontal skull of 20 adult female pigs and covered with a resorbable collagen membrane. Animals were sacrificed after 2 and 6 months. Specimens were histologically and histomorphometrically analysed focusing on the amount of vital bone, residual bone substitute material and connective tissue. Furthermore, the amount of expression of bone matrix proteins (collagen type I and osteocalcin) and de novo vessel formation (von Willebrand factor) were quantified by immunohistochemistry. Results: Significantly more allogeneic bone blocks failed for both evaluation time points (p < 0.05). Allogeneic blocks showed significantly less vital bone with more connective tissue formation compared to autologous bone blocks. Increased vessel formation could be detected for both evaluation time points in the contact area of autologous bone with local bone. The expression of collagen type I and osteocalcin was significantly lower in the allogeneic bone graft. Conclusions: Allogeneic cancellous bone blocks showed a significantly higher failure rate compared to autologous bone blocks. Allogeneic bone blocks seemed to negatively affect bone formation or negatively influence the host in the long term, and increased connective tissue formation and block loss should be anticipated. Clinical relevance: In order to maintain patient safety and treatment success clinicians should be persuaded to make a conscious choice of the applied biomaterials with regard to their components and structure.
CRIS-Team Scopus Importer:2019-12-27
Keywords: Allogeneic bone block; Animal model; Bone substitutes; Histomorphometry; Immunohistochemistry

Peculiarities in the panoramic radiograph of patients with secondary hyperparathyroidism due to terminal renal disease: a radiologic controlled comparative study - Möst, Tobias; Jahn, Arne Eric; Heller, Katharina M.; Schiffer, Mario; Adler, Werner; Rohde, Maximilian; Weber, Manuel; Kesting, Marco Rainer; Lutz, Rainer (Oral Radiology, 2022)
Objectives The present radiological observational controlled study aims to evaluate the impact of secondary hyperparathyroidism (SHPT) due to chronic kidney disease (CKD) as well as the duration of dialysis on the mineralization of the mandible by standardized qualitative evaluation of digital panoramic radiographs. Methods Panoramic radiographs of CKD patients with SHPT and healthy controls were used for the qualitative analysis of the mandibular cortical index (MCI), the trabecular bone pattern (TBP), and calcification and resorption foci. Radiomorphometric indices were correlated to biochemical parameters and the duration of dialysis using the Spearman Rho test. Group comparisons were conducted using the Mann-Whitney U test and Fisher's exact test at a significance level of alpha <= 0.05. Interrater reliability of two physicians was estimated using Cohen's kappa. Results Inclusion and exclusion criteria were fulfilled by N = 41 patients. Statistically significant differences in the MCI (p < 0.001) as well as the TBP (p = 0.002) could be detected for the experimental group in comparison to the healthy control group. Focusing on calcification and resorption foci, no statistically significant difference could be detected between the groups (p = 0.244). The level of the detected parathyroid hormone (PTH) significantly correlated with TBP (Rho = 0.338; p = 0.031), while no significant relationship between TBP and the duration of the dialysis could be found. Conclusions Patients with SHPT due to CKD show statistically significant bone changes in the panoramic radiograph, whereby the grade of trabecular bone change correlates to PTH values.
CRIS-Team WoS Importer:2022-05-20

Prevalence of carotid artery calcification detected by different dental imaging techniques and their relationship with cardiovascular risk factors, age and gender - Möst, Tobias; Winter, Linus; Ballheimer, Yili Elisabeth; Kappler, Christian; Schmid, Magdalena; Adler, Werner; Weber, Manuel; Kesting, Marco Rainer; Lutz, Rainer (BMC Oral Health, 2023)
Background: Atherosclerosis and its secondary diseases display a major threat to patient’s health. Sequelae, like carotid artery calcification (CAC), usually develop over decades and remain asymptomatic for a long time, making preventive measures to reduce mortality and morbidity extremely important. Through panoramic radiography (PR) and cone beam computed tomography (CBCT), dentists may have helpful tools in aiding the holistic care of patients. In this context, the correlation of atherosclerotic risk factors and CAC development have not yet been sufficiently investigated. Thus, the aim of this observational radiological study was to evaluate the diagnostic value of PR compared with CBCT for the detection of CAC in patients older than 60 years. The radiological findings were correlated with gender, age, and cardiac risk factors. Methods: PRs and CBCTs of N = 607 patients were used for the qualitative analysis and compared. Basic patient information such as age, gender, body mass index (BMI), smoking history as well as patient’s detailed medical history, including heart disease and cardiovascular risk factors such as hypercholesterolemia, arterial hypertension and diabetes mellitus type II were documented and their relation to CAC provided by radiological data was estimated in the form of odds ratios (OR), which were calculated using logistic regression models. Proportions of CAC in different risk groups were compared using Fisher’s exact test, the significance level was set to α ≤ 0.05. The interrater reliability of two physicians was estimated using Cohen’s kappa. Results: With an accuracy of 90.6%, a sensitivity of 67.5% and a specificity of 99.5% compared to CBCT, PR was a reliable method for the diagnosis of CAC. The overall detection rate for CAC was 27.8% across all age groups. Age (OR: 1.351; p = 0.021), the male sex (OR: 1.645; p = 0.006), arterial hypertension (OR: 2.217; p = < 0.001), heart disease (OR: 1.675; p = 0.006), hypercholesterolemia (OR: 1.904; p = 0.003) and chronic obstructive pulmonary disease (OR: 2.016; p = 0.036) were statistically significant risk factors. When correlated, neither history of stroke nor nicotine abuse showed any statistical significance. Conclusions: Due to the capabilities of PR in the diagnosis of CAC, dentists can play a vital role in the early diagnosis of vascular disease. Awareness should therefore be raised among dentists regarding the detection of CAC in patients over 60 years of age, with a particular focus on those with arterial hypertension and hypercholesterolaemia.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Atherosclerotic risk factors; Carotid artery calcification; Cone beam computed tomography (CBCT); Panoramic radiography (PR)

Retrospective three-dimensional analysis of bone resorption volumes of free microvascular scapular and fibular grafts - Taxis, Jürgen; Nobis, Christopher-Philipp; Grau, Elisabeth; Kesting, Marco Rainer; Möst, Tobias (British Journal of Oral and Maxillofacial Surgery, 2022)
Defects in head and neck regions are standardly treated with microvascular grafts, such as free scapular (SFF) and fibular flaps (FFF), which are subject to a certain amount of bone resorption over time. The aim of this study was the 3-dimensional evaluation of bone resorption volume in both grafts. Over a period of 10 years, computed tomograms (CT) of patients with mandibular reconstructions with SFFs and FFFs were examined. The respective grafts were segmented as well as 3-dimensionally measured. Furthermore, factors such as gender, age, nicotine abuse, previous disease with type 2 diabetes, and adjuvant therapies, were examined for their influence. A total of 211 CT scans from 67 patients (40 SFFs and 27 FFFs) were included in the study. SFFs showed slightly higher median bone volumes (87.60% at 730 days and 86.55% at 1500 days) than FFFs (84.40% at 730 days and 82.10% at 1500 days). When final volumes were considered, FFFs had higher mean volume values (88.22%) than SFFs (83.82%), with significant correlation between resorption volume and time progression (r = 0.357, p = 0.024). All previously mentioned factors had no significant effect on bone resorption. Bone volumes of FFFs showed postoperative volume reductions similar to those of SFFs, with isolated SFFs having markedly lower volume values. The choice of a microvascular graft for reconstruction in the mandible proves difficult regarding bone resorption. The presented results may support decisions about future transplantations.
CRIS-Team Scopus Importer:2022-12-30
Keywords: Bone resorption; Bone volume; Fibula; Microvascular graft; Scapula; Segmentation

Risikopatienten in der Implantologie - Möst, Tobias; Schlegel, Karl Andreas; Lutz, Rainer; Schmitt, Christian (Implantologie, 2015)
Today, the use of dental implants represents a reliable treatment option for functional and esthetic rehabilitation of edentulous or partially edentulous jaws. However, patient-related risk factors may contraindicate surgical treatment and can consequently have an impact on implant survival and success rates. Patients with metabolic diseases (eg, diabetes) or patients that have previously undergone radiation therapy are affected. Untreated diabetes or irradiation can negatively influence bone turnover and healing and can lead to implant failure. In addition, there are some further risk factors especially linked to older patients that may limit implant success, particularly for the multimorbid patient with pharmacologic issues due to medications as well as cognitive and motor limitations. A basic internistic and pharmacologic understanding as well as an interdisciplinary treatment between the dental specialist and the physician is mandatory for success.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Anticoagulation; Diabetes mellitus; Elderly patient; Irradiation

The colocalizations of pulp neural stem cells markers with dentin matrix protein-1, dentin sialoprotein and dentin phosphoprotein in human denticle (pulp stone) lining cells - Korkmaz, Yüksel; Imhof, Thomas; Kämmerer, Peer W.; Bloch, Wilhelm; Rink-Notzon, Svenja; Möst, Tobias; Weber, Manuel; Kesting, Marco Rainer; Galler, Kerstin M.; Deschner, James (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Background: The primary dentin, secondary dentin, and reactive tertiary dentin are formed by terminal differentiated odontoblasts, whereas atubular reparative tertiary dentin is formed by odontoblast-like cells. Odontoblast-like cells differentiate from pulpal stem cells, which express the neural stem cell markers nestin, S100β, Sox10, and P0. The denticle (pulp stone) is an unique mineralized extracellular matrix that frequently occurs in association with the neurovascular structures in the dental pulp. However, to date, the cellular origin of denticles in human dental pulp is unclear. In addition, the non-collagenous extracellular dentin matrix proteins dentin matrix protein 1 (DMP1), dentin sialoprotein (DSP), and dentin phosphoprotein (DPP) have been well characterized in the dentin matrix, whereas their role in the formation and mineralization of the denticle matrix remains to be clarified. Methods: To characterize the formation of denticle, healthy human third molars (n = 59) were completely sectioned and evaluated by HE staining in different layers at 720 µm intervals. From these samples, molars with (n = 5) and without denticles (n = 8) were selected. Using consecutive cryo-sections from a layer containing denticles of different sizes, we examined DMP1, DSP, and DPP in denticle lining cells and tested their co-localizations with the glial stem cell markers nestin, S100β, Sox10, and P0 by quantitative and double staining methods. Results: DMP1, DSP and DPP were found in odontoblasts, whereas denticle lining cells were positive only for DMP1 and DSP but not for DPP. Nestin was detected in both odontoblasts and denticle lining cells. S100β, Sox10, and P0 were co-localized with DMP1 and DSP in different subpopulations of denticle lining cells. Conclusions: The co-localization of S100β, Sox10, and P0 with DMP1 and DSP in denticle lining cells suggest that denticle lining cells are originated from glial and/or endoneurial mesenchymal stem cells which are involved in biomineralization of denticle matrix by secretion of DMP1 and DSP. Since denticles are atubular compared to primary, secondary, reactionary tertiary dentin and denticle formed by odontoblasts, our results suggest that DPP could be one of the proteins involved in the complex regulation of dentinal tubule formation.
CRIS-Team Scopus Importer:2021-09-10
Keywords: D; Denticle lining cells; DMP1; Endoneurial mesenchymal stem cells; Glial stem cells; P0; Sox10

The effect of polyethylenglycol gel on the delivery and osteogenic differentiation of homologous tooth germ–derived stem cells in a porcine model - Ramazanoglu, Mustafa; Möst, Tobias; Ercal, Pınar; Polyviou, Zacharias; Herrmann, Kathrin; Gurel Pekozer, Gorke; Molenberg, Aart; Lutz, Rainer; Torun Kose, Gamze; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Clinical Oral Investigations, 2020)
Objectives: The aim of this study was to investigate if bone regeneration can be promoted by homologous transplantation of STRO-1 sorted (STRO-1+) porcine tooth germ mesenchymal stem cells (TGSCs) with the combination of polyethylenglycol (PEG)-based hydrogel and biphasic calcium phosphate (BCP) scaffolds. Material and methods: TGSCs were isolated from impacted third molars of domestic pigs. Nine critical-sized defects were created as (1) untreated defect; filled with (2) autogenous bone; (3) BCP + PEG; (4) BCP + PEG + unsorted TGSCs; (5) BCP + unsorted TGSCs; (6) BCP + PEG + STRO-1-sorted TGSCs; (7) BCP + STRO-1-sorted TGSCs; (8) BCP + PEG + osteogenic induced unsorted TGSCs; and (9) BCP + PEG + osteogenic induced STRO-1-sorted TGSCs in 20 domestic pigs. CM-DiI labelling was used to track cells in vivo. Histomorphometric assessment of new bone formation was achieved by toluidine blue O staining and microradiography after 1, 2, 4 and 12 weeks posttransplantation. Results: Complete healing was achieved in all defects although defects with PEG hydrogel presented better bone formation while STRO-1+ and unsorted TGSCs showed similar ability to form new bone after 12 weeks. Transplanted cells were seen in defects where PEG hydrogel was used as carriers in contrast to defects treated with cells and only bone grafts. Conclusions: PEG hydrogel is an efficient carrier for homologous stem cell transplantation. TGSCs are capable of promoting bone healing in critical-sized defects in combination with bone graft and PEG hydrogel. Clinical relevance: This study provides information about the importance of the delivery vehicle for future translational stem cell delivery approaches.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Bone regeneration; Mesenchymal stem cells; Polyethylenglycol hydrogel; Tissue scaffolds; Tooth germ

The Immune Checkpoint Receptor CD96: A Local and Systemic Immune Modulator in Oral Cancer? - Trumet, Leah; Weber, Manuel; Hahn, Alina; Kunater, Lina; Geppert, Carol-Immanuel; Glajzer, Jacek; Struckmeier, Ann-Kristin; Möst, Tobias; Lutz, Rainer; Kesting, Marco Rainer; Ries, Jutta (Cancers, 2023)
Background: As immunotherapy of oral squamous cell carcinomas (OSCCs), using PD1 inhibitors, is only efficient in a small proportion of patients, additional immune checkpoints need to be identified as potential therapeutic targets. There is evidence that a blockade of CD96 might positively affect the anti-tumor immune response. The aim of this study was to analyze the gene and protein expression of CD96 in the tissue and peripheral blood of OSCC patients compared to healthy controls, while also checking for potential associations with a differential expression to the histomorphological parameters. In addition, possible correlations with the expression of PD1 and PD-L1 as well as the macrophage markers CD68 and CD163 should be tested to obtain further insights into the potential effectiveness of combined checkpoint blockage. Material and Methods: For real-time quantitative polymerase chain reaction (RT-qPCR), a total of 183 blood and tissue samples, divided into a patient and a control group, were included. Additionally, 141 tissue samples were examined by immunohistochemistry (IHC). The relative expression differences between the groups were calculated using statistical tests including the Mann–Whitney U test and AUC method. The Chi-square test was used to determine whether CD96 overexpression in individual samples is associated with malignancy. Correlation analysis was performed using the Spearman correlation test. Results: There was a significant CD96 mRNA and protein overexpression in the OSCC group compared to the controls (p = 0.001). In contrast, CD96 mRNA expression in the peripheral blood of the OSCC patients was significantly lower compared to the control group (p = 0.007). In the Chi-square test, the OSCC tissue samples showed a highly significant upregulation of CD96 mRNA expression (p < 0.001) and protein expression (p = 0.005) compared to the healthy mucosa. CD96 mRNA and protein expression correlated significantly (p = 0.005). In addition, there was a significant positive correlation of CD96 expression with PD1 (p ≤ 0.001), PD-L1 (p ≤ 0.001), and CD163 (p = 0.006) at the mRNA level. Conclusions: CD96 expression in the tumor tissue and peripheral blood of OSCC patients is differentially regulated and appears to be a relevant immune checkpoint.
CRIS-Team Scopus Importer:2023-04-28
Keywords: HNSCC; immune checkpoints; immunotherapy; OSCC; PD-1; PD-L1

The influence of nanoporous anodic aluminum oxide on the initial adhesion of Streptococcus mitis and mutans - Taxis, Jürgen; von Wilmowsky, Cornelius; Pedimonte, Birgit; Beuscher, Horst-Ulrich; Ries, Jutta; Kesting, Marco Rainer; Möst, Tobias (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2019)
The use of nanoscale surface modifications offers a possibility to regulate the bacterial adherence behavior. The aim of this study was to evaluate the influence of nanoporous anodic aluminum oxide of different pore diameters on the bacterial species Streptococcus mitis and Streptococcus mutans. Nanoporous anodic aluminum oxide (AAO) surfaces with an average pore diameter of 15 and 40 nm, polished pure titanium and compact aluminum oxide (alumina) samples as reference material were investigated. S. mitis and mutans were evaluated for initial adhesion and viability after an incubation period of 30 and 120 min. After 30 min a significantly reduced growth of S. mitis and mutans on 15 nm samples compared to specimens with 40 nm pore diameter, alumina and titanium surfaces could be observed (p <.001). Even after 120 min incubation there was a significant difference between the surfaces with 15 nm pore diameter and the remaining samples (p <.001). AAO surfaces with a small pore diameter have an inhibitory effect on the initial adhesion of S. mitis and mutans. The use of such pore dimensions in the area of the implant shoulder represents a possibility to reduce the adhesion behavior of these bacterial species.
CRIS-Team Scopus Importer:2019-12-03
Keywords: biofilm; initial adhesion; nanoporous anodic aluminum oxide; Streptococcus mitis; Streptococcus mutans

The special developmental biology of craniofacial tissues enables the understanding of oral and maxillofacial physiology and diseases - Weber, Manuel; Wehrhan, Falk; Deschner, James; Sander, Janina; Ries, Jutta; Möst, Tobias; Bozec, Aline; Gölz, Lina; Kesting, Marco Rainer; Lutz, Rainer (International Journal of Molecular Sciences, 2021)
Maxillofacial hard tissues have several differences compared to bones of other localiza-tions of the human body. These could be due to the different embryological development of the jaw bones compared to the extracranial skeleton. In particular, the immigration of neuroectodermally differentiated cells of the cranial neural crest (CNC) plays an important role. These cells differ from the mesenchymal structures of the extracranial skeleton. In the ontogenesis of the jaw bones, the development via the intermediate stage of the pharyngeal arches is another special developmental feature. The aim of this review was to illustrate how the development of maxillofacial hard tissues occurs via the cranial neural crest and pharyngeal arches, and what significance this could have for relevant pathologies in maxillofacial surgery, dentistry and orthodontic therapy. The pathogenesis of various growth anomalies and certain syndromes will also be discussed.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Cranial neural crest; Developmental biology; Maxillofacial development; Orthodontics

Three-dimensional assessment after maxillary sinus grafting with a bovine, a porcine, and a synthetic bone substitute material. A randomized controlled clinical trial. - Schmitt, Christian; Wiesheu, Simon; Schlegel, Karl Andreas; Adler, Werner; Kesting, Marco Rainer; Matta, Ragai; Möst, Tobias (International Journal of Computerized Dentistry, 2024)
AIM: The present randomized controlled clinical trial focused on graft volume alterations after sinus floor augmentation with a deproteinized bovine bone mineral (DBBM; Bio-Oss), a deproteinized porcine bone mineral (DPBM; THE Graft), or a biphasic calcium phosphate (BCP; Osopia) material. MATERIALS AND METHODS: A total of 28 patients with edentulism in the posterior maxilla with ≤ 5 mm of residual bone height received a two-staged external sinus grafting procedure with DBBM, DPBM, or BCP. Three CBCT scans were performed: 1) prior to surgery (CBCT1); 2) directly after surgery (CBCT2); 3) after a healing period of 4 to 6 months, prior to implant placement (CBCT3). The CBCT scans were used to analyze volumetric alterations of the sinus grafts by virtual 3D model matching of CBCT1 and CBCT2 (situation after sinus grafting), and CBCT1 and CBCT3 (situation prior to implant placement). RESULTS: The volume of the bone graft in the maxillary sinus (volume [VOL%] directly after grafting rated as 100%) was stable after the healing period in the DBBM (VOL%: 103 ± 4%) and the DPBM (VOL%: 112 ± 23%) groups, with no statistically significant differences regarding 3D measurements. In the BCP group, the grafted volume declined to VOL%: 66 ± 25%, statistically inferior to the DBBM and DPBM groups. CONCLUSIONS: Regarding bone graft stability/volume, the DBBM and DPBM groups showed comparable outcomes. Due to resorption, the BCP group showed inferior bone graft volume after healing (statistically significant) compared with the DBBM and DPBM groups.
EVALuna2:541030

Three-dimensional assessment of upper airway changes associated with mandibular positional deviations following fibula free flap reconstruction - Schulz, Katja; Matta, Ragai; Nobis, Christopher-Philipp; Möst, Tobias; Kesting, Marco Rainer; Lutz, Rainer (Clinical Oral Investigations, 2024)
Objectives: Fibula free flaps (FFF) are the standard approach to mandibular reconstruction after partial resection, with the goal of restoring aesthetics and masticatory function. The graft position affects both and must be carefully selected. Correlations between sagittal positioning and upper airway anatomy are known from orthognathic surgery. This study aims to evaluate changes in mandibular position and upper airway anatomy after reconstructive surgery with FFF and corresponding correlations. Materials and methods: Mandibular position after reconstruction was evaluated using three-dimensional datasets of pre- and postoperative computed tomography scans of patients treated between 2020 and 2022. Three-dimensional measurements were performed on both condyles and the symphyseal region. Changes in upper airway volume and minimum cross-sectional area (minCSA) were analysed. Intra-rater reliability was assessed. Correlations between changes in upper airway anatomy and sagittal mandibular position were tested. Results: The analysis included 35 patients. Intra-rater reliability was good to excellent. Condylar deviations and rotations were mostly rated as small. Changes in symphyseal position were considerably greater. Median airway volume decreased in the oropharynx and hypopharynx. Posterior deviation of the symphysis was associated with a decreasing minCSA in the hypopharynx and vice versa. Conclusions: The overall accuracy of mandibular reconstructions with FFF is high, but there is room for optimization. The focus of research should be extended from masticatory to respiratory rehabilitation. Clinical relevance: Effects on respiratory function should be considered prior to graft positioning. The clinical relevance of upper airway changes within the complex rehabilitation of reconstructive surgery patients needs to be further investigated.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Fibula; Mandible; Mandibular reconstruction; Three-dimensional evaluation; Upper airway anatomy

Use of CAD-based pre-bent implants reduces theatre time in orbital floor reconstruction: results of a prospective study - von Wilmowsky, Cornelius; Schwertner, Maximilian; Nkenke, E.; Möst, Tobias; Adler, Werner; Ebker, T. (British Journal of Oral and Maxillofacial Surgery, 2020)
In this prospective study we evaluated the duration of insertion and the accuracy of fitting of computer-aided design (CAD)-based pre-bent orbital floor plates compared with non-preformed orbital plates in reconstruction of the orbital floor. Thirty-six patients with unilateral fractures of the orbital floor were included; pre-bent plates were used in 25 and non-preformed plates in 11. Preoperative computed tomography (CT) scans were used for CAD of individualised implants. The anatomy of the affected orbit was virtually reconstructed “slice by slice”. Individually pre-bent plates were generated using a stereolithographic model of the reconstructed orbit. The mean (SD) duration of insertion was significantly reduced when pre-bent orbital plates were used (5.5 (5.4) min) compared with non-preformed meshes (11.1 (7.7) min). The congruence of pre-bent plates to the infraorbital rim did not differ from that of non-preformed plates. The accuracy of fit was rated as “accurate” in 24 cases. CAD-based individualised titanium meshes reduce theatre time compared with non-preformed orbital plates. Our results confirm the efficacy of CAD-based pre-bent plates in reconstruction of the orbital floor.
CRIS-Team Scopus Importer:2020-07-10
Keywords: computer-aided design; individually pre-bent titanium mesh; intraoperative time comparison; orbital floor fracture; orbital floor reconstruction

Zoledronate causes a systemic shift of macrophage polarization towards M1 in vivo - Weber, Manuel; Homm, Andi; Müller, Stefan; Frey, Silke; Amann, Kerstin Ute; Ries, Jutta; Geppert, Carol-Immanuel; Preidl, Raimund; Möst, Tobias; Kämmerer, Peer W.; Kesting, Marco Rainer; Wehrhan, Falk (International Journal of Molecular Sciences, 2021)
Background: Immunomodulatory properties of bisphosphonates (BP) are suggested to contribute to the development of medication‐associated osteonecrosis of the jaw (MRONJ). Further-more, bisphosphonate‐derived immune modulation might contribute to the anti‐metastatic effect observed in breast cancer patients. Macrophages are potential candidates for the mediation of immunomodulatory effects of bisphosphonates. The study aimed to investigate the influence of bisphosphonates alone and in combination with surgical trauma on systemic macrophage polarization (M1 vs. M2) using an in vivo rat model. Methods: A total of 120 animals were divided into four groups. Groups 2 and 4 were treated with 8 × 40 μg/kg body weight of the BP Zoledronate i.p. (week 0–7). Groups 3 and 4 were exposed to surgical trauma (week 8, tooth extraction + tibia fracture), whereas in Group 1 neither medication nor surgical trauma was applied. After 8, 10, 12 and 16 weeks, skin, lung and spleen were immunohistochemically examined for macrophage polarization via expression analysis of CD68, CD163 and iNOS using a tissue microarray (TMA). Results: A significant shift of macrophage polarization towards M1 was observed in skin, spleen and lung tissue of animals, with and without surgical trauma, treated with BP when compared to those without BP application. Surgical trauma did not cause a significant increase towards M1 polarization. Conclusions: BP application leads to a systemic pro‐inflammatory situation in vivo, independent of surgical trauma, as evidenced by the shift in macrophage polarization towards M1 in various somatic tissues. This provides a possible explanation for the clinically observed anti‐tumor effect of bisphosphonates and might also contribute to pathogenesis of MRONJ.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Antiresorptives; Bisphosphonate; Immune modulation; M1; M2; Macrophage polarization; Zoledronate